Pengaruh Brand Image, Pelayanan dan Word Of Mouth Terhadap Keputusan Konsumen PT. Jaladara Jaya Trans Klaten - Hidayat, Yusuf Alfian; Istiatin, Istiatin; Hartono, Sri (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The research design uses a quantitative descriptive design. The population is consumers of PT. Jaladara Jaya Trans Klaten and a sample of 97 people using the saturated sample technique, where the entire population is sampled. Linear regression test is used to analyze. The result is that brand image, service and word of mouth each influence PT. Jaladara Jaya Trans Klaten. Keywords: brand image, service, word of mouth, consumer decision